Detecting Mechanisms of Karyotype Evolution in Heterotaxis (Orchidaceae). - Ana Paula Moraes; André Olmos Simões; Dario Isidro Ojeda Alayon; Fábio de Barros; Eliana Regina Forni-Martins (PLoS ONE, 2016)
The karyotype is shaped by different chromosome rearrangements during species evolution. However, determining which rearrangements are responsible for karyotype changes is a challenging task and the combination of a robust phylogeny with refined karyotype characterization, GS measurements and bioinformatic modelling is necessary. Here, this approach was applied in Heterotaxis to determine what chromosome rearrangements were responsible for the dysploidy variation. We used two datasets (nrDNA and cpDNA, both under MP and BI) to infer the phylogenetic relationships among Heterotaxis species and the closely related genera Nitidobulbon and Ornithidium. Such phylogenies were used as framework to infer how karyotype evolution occurred using statistical methods. The nrDNA recovered Ornithidium, Nitidobulbon and Heterotaxis as monophyletic under both MP and BI; while cpDNA could not completely separate the three genera under both methods. Based on the GS, we recovered two groups within Heterotaxis: (1) "small GS", corresponding to the Sessilis grade, composed of plants with smaller genomes and smaller morphological structure, and (2) "large GS", corresponding to the Discolor clade, composed of plants with large genomes and robust morphological structures. The robust karyotype modeling, using both nrDNA phylogenies, allowed us to infer that the ancestral Heterotaxis karyotype presented 2n = 40, probably with a proximal 45S rDNA on a metacentric chromosome pair. The chromosome number variation was caused by ascending dysploidy (chromosome fission involving the proximal 45S rDNA site resulting in two acrocentric chromosome pairs holding a terminal 45S rDNA), with subsequent descending dysploidy (fusion) in two species, H. maleolens and H. sessilis. However, besides dysploidy, our analysis detected another important chromosome rearrangement in the Orchidaceae: chromosome inversion, that promoted 5S rDNA site duplication and relocation.